China's Innovative ISDS Mechanisms and Their Implications. (27th August 2018) - Chen, Huiping
Abstract : International arbitration before Western-based institutions is the dominant mode of investor-state dispute settlement (ISDS). The Washington-based International Centre for Settlement of Investment Disputes (ICSID), the Hague-based Permanent Court of Arbitration, the Arbitration Institute of the Stockholm Chamber of Commerce, and the International Court of Arbitration of the Paris-based International Chamber of Commerce handle the vast majority of the world's international investment disputes. ICSID alone administers over sixty percent of the cases, while the others account for an additional twenty percent. Yet China has begun to innovate in ISDS over the last few years. These innovations have taken three main forms. The first is the extension of the jurisdiction of existing commercial arbitral institutions in China to cover foreign investment disputes. The second is the creation of new Chinese courts to possibly handle contractual investment disputes. The third is the formation of joint arbitration centers with states in regions where China invests heavily, such as Africa. This essay describes these changes and argues that they should be understood as reflecting an important facet of China's broader international strategy. In particular, the recent innovations aim to furnish adequate protection to Chinese investors in foreign countries, particularly developing states; actively shape international discourses on international investment law; and offer alternative, Chinese-initiated institutions that will break the monopoly of the West.